The Relationship Between Workload and Stress Level in Emergency Department of RSU Kabupaten Tangerang - Shieva Nur Azizah Ahmad; Bunga Hidinopti (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
The burden of nurses is a dimension of all this activity or activities performed by a nurse for serving in a unit of health services. Service fast and exactly is needed in the service of the emergency room that can lead to the workload in the nurse, like encountering patients with various complaints of different diseases and patients come with the conditions are not stable, with the families of patients who can't wait, in addition to monitor and entering the patient's condition repeatedly is a unique and very unexpected because it can affect the stress. The research aims to identify how the workload with the stress level of work a nurse in Emergency Department RSU kabupaten Tangerang. The design of the deskriptif koleration with the cross sectional. Study sample as much as 40 of the respondents a nurse using the method of non probabiliti sampling techniques purposive sampling in accordance with the criteria for inclusion and eksklusi. Instruments in this study uses a questionnaire on the workload and level of job stress. The results showed the burden of hard work with the stress level of hard work as much as 15 respondents (88.2 %). The test results Chi Square to show p-value 0.002 (α < 0.05) that Ho is rejected and Ha is in, there is the relationship between workload with the stress level of work a nurse in Emergency Department RSU kabupaten Tangerang. Keywords: Level of Stress, Workload